2008
DOI: 10.5194/acp-8-491-2008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global water vapour trends from satellite measurements in the visible spectral range

Abstract: Abstract. Global water vapour total column amounts have been retrieved from spectral data provided by the Global Ozone Monitoring Experiment (GOME) flying on ERS-2, which was launched in April 1995, and the SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) onboard ENVISAT launched in March 2002. For this purpose the Air Mass Corrected Differential Optical Absorption Spectroscopy (AMC-DOAS) approach has been used. The combination of the data from both instruments provides us with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 29 publications
1
66
1
Order By: Relevance
“…As most the water vapour is found in the troposphere, increasing its volume mixing ratio towards the surface, a large impact of the shielding effect on the satellite TWVC retrievals is expected (Mieruch et al, 2008(Mieruch et al, , 2010. Thus, some retrieval algorithms make use of a cloud correction method to take into account the water vapour present below the clouds -e.g.…”
Section: Dependence Of the Differences On Cloud Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…As most the water vapour is found in the troposphere, increasing its volume mixing ratio towards the surface, a large impact of the shielding effect on the satellite TWVC retrievals is expected (Mieruch et al, 2008(Mieruch et al, , 2010. Thus, some retrieval algorithms make use of a cloud correction method to take into account the water vapour present below the clouds -e.g.…”
Section: Dependence Of the Differences On Cloud Parametersmentioning
confidence: 99%
“…Kaufman and Gao, 1992;Bauer and Schlüssel, 1993;Noël et al, 1999Noël et al, , 2004Maurellis et al, 2000;Wagner et al, 2006;Li et al, 2006;Deeter, 2007;Lang et al, 2007;Mieruch et al, 2008;Pougatchev et al, 2009). Within this framework, the European satelliteborne atmospheric sensor Global Ozone Monitoring Experiment 2 (GOME-2) aboard the Meteorological Operational satellite program (MetOp-A and MetOp-B) provides the potential for a detailed analysis of the global distribution of the atmospheric water vapour .…”
mentioning
confidence: 99%
“…So it is not surprising that a number of publications have noted that statistically significant, long-term trends in climate variables are difficult to derive from satellite data because of problems with satellite intercalibration and sensor drift (Hurrel andTrenberth, 1997, 1998;Christy et al, 1998;Wenz andSchabel, 1998, Trenberth et al, 2007). First satellite based IWV trend studies via ERS-2/GOME and ENVISAT/SCIAMACHY data were reported only recently (Wagner et al, 2006;Mieruch et al, 2008).…”
Section: R Sussmann Et Al: Trends In Column-integrated Water Vapor mentioning
confidence: 99%
“…Various wavelength windows have been explored: around 650 nm (Wagner et al, 2003, around 700 nm (Noël et al, , 2005Mieruch et al, 2008), and around 590 nm (Maurellis et al, 2000;Lang et al, 2003). The advantage of using these windows is that the measurements are also sensitive to the boundary layer, where most of the water vapour resides.…”
Section: H Schrijver Et Al: Water Vapour Columns From Sciamachy 23mentioning
confidence: 99%